9(x+3)-3x=55

Simple and best practice solution for 9(x+3)-3x=55 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x+3)-3x=55 equation:



9(x+3)-3x=55
We move all terms to the left:
9(x+3)-3x-(55)=0
We add all the numbers together, and all the variables
-3x+9(x+3)-55=0
We multiply parentheses
-3x+9x+27-55=0
We add all the numbers together, and all the variables
6x-28=0
We move all terms containing x to the left, all other terms to the right
6x=28
x=28/6
x=4+2/3

See similar equations:

| 55+26x-1=90 | | |2x-7|=|x+4| | | 3.8x-47=1.3x+8 | | -8=-4(v+19) | | 0.6x+0.9=-0.2x-2.3 | | 6(4n-2)=40-2n | | 31=4(u-6)+7u | | x-1=1.48 | | 3/7=2/5x | | 17-s/4=-10s= | | -(j-6)=-3 | | x+3.6=9.2 | | -2y-3-(-4y+5+(-y+2-(3y-1)+2-5))=-(y-4) | | 2=7(w+2)-4w | | 55+26×-1=80x | | 11=6x-1+6x | | -8=-5v+7(v-4) | | -11-2k=1-8k | | 11x-5(2x-1)=5(6-x)+3 | | 7c-(1/3)=(7/9) | | 7x+2x-9=2(4x+8) | | -11-2k=-1-8k | | -7(9n+8)=-31-4n | | -0.67(x+2)=0.17(x+6) | | 90+.50m=50+.60m | | 40(p-4.5)=112 | | .16x+21=x | | 4-8X=9x+20 | | 3h=7(2÷7-3÷7h)-10 | | 8x-9x=-29 | | x/4-5=6-x/4 | | 4/5-x=2 |

Equations solver categories